PENGEMBANGAN ALAT PERMAINAN EDUKATIF (APE) ULAR TANGGA UNTUK MENINGKATKAN KEMAMPUAN MOTORIK KASAR ANAK USIA 4-5 TAHUN - Fitri Rismadani; Defni Satria; Rita Kurnia (Generasi Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2022)
This study aims to determine the development and feasibility of the snake ladder educational game tool (APE) to improve the gross motor skills of children aged 4-5 years. The research method used is Research and Development (RND), which produces a product and can test the effectiveness of the product. The data analysis technique used by the researcher in this study is a quantitative descriptive analysis technique. Data analysis for product feasibility uses the assessment of the results obtained from learning media experts and material experts in the form of a questionnaire instrument (questionnaire). The resulting product development in the form of an educational game tool (APE) snake ladder made of banner printing material with a size of 2.4 x 3 meters is used as a learning medium to improve gross motor skills of children aged 4-5 years. The validation results obtained in the development of the snake and ladder educational game tool (APE) are very satisfying. The results of material validation are in the "very feasible" category. While the results of media validation are having a "very feasible" validation category. The results of the two validation categories show "very feasible", therefore the development of the snake and ladder educational game tool (APE) is certainly very suitable to be used to improve the gross motor skills of children aged 4-5 years.